Effect of Structural Variations on the Thermophysical Properties of Protic Ionic Liquids: Insights from Experimental and Computational Studies - Khan, A.S. (American Chemical Society, 2017)
In this work, new protic ionic liquids (PILs) based on 1-methylimidazolium/1-propanenitrileimidazolium cations with hydrogen sulfate, methanesulfonate, trifluoromethanesulfonate, para-toluenesulfonate, trifluoroacetate, and acetate anions were synthesized. The structures and purity of the products were confirmed by using 1H and 13C NMR and CHNS elemental analysis. The effect of structural variations on the thermophysical properties, namely, refractive index, density, and viscosity, was evaluated in a wide temperature range. The viscosity and density values were measured within the temperature range of 293.15-373.15 K. The density values were used further to calculate more properties like thermal expansion coefficient, molecular volume, standard entropy, and the lattice energy. Moreover, the experimental values of viscosity were used for the calculation of activation energy. Refractive indices were measured within the temperature range of 293.15-323.15 K, and these values were also used in the calculation of electronic polarizability. Acid numbers of the prepared PILs were measured and correlated with their structure moiety. In addition, the density functional theory (DFT) calculations were performed to get a deeper insight into the effect of structural variations of the ion pairs on their physical properties. © 2017 American Chemical Society.